5/2(-3x+2)=3/4X+6

Simple and best practice solution for 5/2(-3x+2)=3/4X+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/2(-3x+2)=3/4X+6 equation:


x in (-oo:+oo)

(5/2)*(2-3*x) = (3/4)*X+6 // - (3/4)*X+6

(5/2)*(2-3*x)-((3/4)*X)-6 = 0

(5/2)*(2-3*x)+(-3/4)*X-6 = 0

5/2*(2-3*x)+(-3*X)/4-6 = 0

(5/2*4*(2-3*x))/4+(-3*X)/4+(-6*4)/4 = 0

5/2*4*(2-3*x)-3*X-6*4 = 0

20-3*X-30*x-24 = 0

-3*X-30*x-4 = 0

(-3*X-30*x-4)/4 = 0

(-3*X-30*x-4)/4 = 0 // * 4

-3*X-30*x-4 = 0

-3*X-30*x-4 = 0 // + -3*X-4

-30*x = -(-3*X-4) // : -30

x = (-(-3*X-4))/(-30)

x = (4-(-3*X))/(-30)

x = (4-(-3*X))/(-30)

See similar equations:

| (2a+5)(s+4)=0 | | 7.38=2(3.14r) | | x/3=192 | | 18t-72+3t=21t+14-10 | | 10x+30(x-2)=340 | | -2x+16=24 | | 18(t-4)+3t=7(3t+2)-10 | | 4n=55 | | (3/17)x=12 | | -(6y+1)-(-5y-3)=1 | | (4x-5)+x=85 | | 2b^2+19b+45=0 | | 1-3(5b-2)=4+-(7b+3) | | 3(x+1)(x-1)-5=3x(x+2) | | -(4/5)x=(8/15) | | 4(y-5)=-5y-38 | | slopem= | | b^2=40-b | | 5x-8=-43 | | 3x-6=-6x+9 | | 2(3x-2)=4(3x+5)-3(x-6) | | N-10=13+5 | | 25+x=30 | | -3/5+1/2 | | (x+2)3=x+14 | | (x+2).3=x+14 | | -8x-7/3=11 | | (x+6)(x+4)-(x-2)(x+1)=30 | | -1.1+(x+3)= | | n=(6n-5g)/11t | | (10x+11)= | | y^3+3y^2-4y=12 |

Equations solver categories